Risk factors in equine transport‐related health problems: A survey of the Australian equine industry. (13th October 2016) - Padalino, B.; Raidal, S. L.; Hall, E.; Knight, P.; Celi, P.; Jeffcott, L.; Muscatello, G.
Summary: Background: Transportation can affect equine health and is a potential source of economic loss to the industry. Objectives: To identify journey (duration, vehicle, commercial or noncommercial) and horse (sex, age, breed, use, amateur or professional status) characteristics associated with the development of transport‐related health problems in horses. Study design: Cross‐sectional online survey. Methods: An online survey was conducted targeting amateur and professional participants in the Australian equine industry; eligible respondents were required to organise horse movements at least monthly. Respondents provided details of the last case of a transport‐related health problem that had affected their horse(s). Associations between type of health problem, journey and horse characteristics were examined with multivariable multinomial regression analysis. Results: Based on 214 responses, health problems were classified as injuries, muscular problems, heat stroke, gastrointestinal and respiratory problems, and death or euthanasia. Respiratory problems were reported most frequently (33.7%), followed by gastrointestinal problems (23.8%) and traumatic injuries (16.3%). The type of health problem was associated with journey duration (P<0.001) and horse breed (P = 0.001). Injuries were more likely to occur on short journeys, whereas more severe illnesses (gastrointestinal and respiratory problems, and death or euthanasia) were more likely to occur on long journeys. Using Standardbreds as the reference group, Thoroughbreds, Arabians and Warmbloods were more likely to experience a severe illness than an injury. Main limitations: Self‐selected participation in the study and the self‐reported nature of transport‐related problems. Conclusions: Horses undertaking journeys of longer than 24 h are at greater risk for the development of severe disease or death. Further studies on long‐haul transportation effects are required to safeguard the welfare of horses moved over long distances.